Rural Collaborative Model for Diabetes Prevention and Management: A Case Study. Issue 6 (November 2017) - Kunz, Susan; Ingram, Maia; Piper, Rosalinda; Wu, Tianne; Litton, Nina; Brady, Joanne; Knudson, Alana
Diabetes disproportionately affects racial and ethnic minorities, rural, and impoverished populations. This case study describes the program components and key lessons learned from implementing Vivir Mejor! (Live Better!), a diabetes prevention and management program tailored for the rural, Mexican American population. The program used workforce innovations and multisector partnerships to engage and activate a rural, mostly Hispanic population. Community health worker (CHW) roles were designed to reach and support distinct populations. Promotoras focused exclusively on health education and patient navigators individually coached patients with chronic disease management issues for the high-risk patient population. To extend diabetes health education to the broader community in Santa Cruz County, promotoras trained lay leaders to become peer educators. Multisector partnerships allowed the program to offer health and social services around diabetes care. The partners also supported provider engagement through continuing education workshops and digital story screening to encourage referrals to the program. Multisector partnerships, including partnering with critical access hospitals, for diabetes management and prevention, as well as using different types of CHWs to implement programs that target high- and low-risk populations are innovative and valuable components of the Vivir Mejor! model.